Differences in Indicators of Malignancy Between Luminal Epithelial Cell Type and Myoepithelial Cell Type of Simple Solid Carcinoma in the Canine Mammary Gland. (November 2014) - Yoshimura, H.; Nakahira, R.; Kishimoto, T. E.; Michishita, M.; Ohkusu-Tsukada, K.; Takahashi, K.
Routinely diagnosed simple solid carcinoma (SSC) of the canine mammary gland comprises a heterogeneous group of tumors. Seventy-two cases that had been diagnosed as SSC based on hematoxylin and eosin–stained tissue sections were reclassified immunohistochemically on the basis of myoepithelial markers p63 and α-smooth muscle actin, as well as a luminal epithelial marker cytokeratin 8. Only 23 cases (32%) were true SSC, composed only of luminal epithelial cells, whereas 11 cases (15%) were malignant myoepithelioma (MM), composed predominantly of myoepithelial cells, and 38 cases (53%) were biphasic carcinoma (BC), characterized by biphasic proliferation of luminal epithelial and basal/myoepithelial components. As the pathological parameters were compared between the reclassified tumor types, infiltrative potential, vascular/lymphatic invasion, lymph node metastasis, and Ki-67 labeling index were higher in true SSC compared with MM and BC, suggesting that the former may exhibit a poorer prognosis compared with the latter two.